MATHEMATICAL THINKING PROCESS IN GRAPH THEORY MATERIAL IN TERMS OF STUDENT LEARNING STYLES - Hetty Patmawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the lack of understanding students have in working on graph theory material problems due to differences in students' thinking processes, and student learning styles when studying discrete mathematics, which requires different thinking with Boolean algebra material. Each student has a different way of thinking skills and learning style. This study uses descriptive qualitative methods so that this study has the objective to find out how the students' mathematical thinking processes in working on graph theory material problems and what obstacles are experienced by students in terms of their learning styles. The focus of research in this study, namely to analyze mathematical thinking processes on graph theory material in terms of student learning styles. The instruments in this study were researchers and also graph theory test questions that were used to view students' thought processes. The research subjects were 5 semester students, as many as 3 people with visual, auditory and kinesnetik learning styles. Then given the problem of graph theory as much as 2 questions, one question in the form of text and another in the form of images. The results show that students with visual learning styles tend to be included in students who have a conceptual thinking process, students with auditory learning styles tend to be included in students who have semi-conceptual thinking processes, while students with kinesthetic learning styles, including students who have computational thinking process . Barriers experienced by students include the lack of understanding of the basic concepts of graph theory and the trajectories and trajectories of Euler and Hamilton.